2022
DOI: 10.22514/jocpd.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

A review on the influence of rapid maxillary expansion and mandibular advancement for treating obstructive sleep apnea in children

Abstract: This article reviews the orthodontic alternatives for treating pediatric obstructive sleep apnea (OSA). OSA is a multifactorial disease that impairs craniofacial growth and the general health of a developing child and negatively worsens their quality of life. Therefore, it is important to timely diagnose and treat OSA to avoid the progress of the disease, which could otherwise lead to systemic, neurocognitive and social consequences in the patients. In the transverse direction, compression of the maxilla could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…How-ever, oral appliances are preferred due to lower pain levels and, in some cases, dissatisfaction with symptom improvement in the alternative method [12]. Research has indicated that patients tend to favor oral appliances over CPAP or other treatments due to the comfort they provide and the resulting improvement in their quality of life [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…How-ever, oral appliances are preferred due to lower pain levels and, in some cases, dissatisfaction with symptom improvement in the alternative method [12]. Research has indicated that patients tend to favor oral appliances over CPAP or other treatments due to the comfort they provide and the resulting improvement in their quality of life [15,16].…”
Section: Introductionmentioning
confidence: 99%